2017
DOI: 10.1126/scitranslmed.aah3560
|View full text |Cite|
|
Sign up to set email alerts
|

Integrated molecular analysis of tumor biopsies on sequential CTLA-4 and PD-1 blockade reveals markers of response and resistance

Abstract: Immune checkpoint blockade produces clinical benefit in many patients. However better biomarkers of response are still needed, and mechanisms of resistance remain incompletely understood. To address this, we recently studied a cohort of melanoma patients treated with sequential checkpoint blockade against cytotoxic T lymphocyte antigen-4 (CTLA-4) followed by programmed death receptor-1 (PD-1), and identified immune markers of response and resistance. Building on these studies, we performed deep molecular profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

25
670
3
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 717 publications
(701 citation statements)
references
References 73 publications
25
670
3
3
Order By: Relevance
“…More recent studies have identified chromosomal alterations as contributing genetic factors of resistance to immunotherapy. 46,47 The relationship of these alterations to PD-L1 expression or specific melanoma subtypes has yet to be defined.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More recent studies have identified chromosomal alterations as contributing genetic factors of resistance to immunotherapy. 46,47 The relationship of these alterations to PD-L1 expression or specific melanoma subtypes has yet to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…More recent studies have identified chromosomal alterations as contributing genetic factors of resistance to immunotherapy. 46,47 The relationship of these alterations to PD-L1 expression or specific melanoma subtypes has yet to be defined.Pure desmoplastic melanomas tend to be characterized by the presence of lymphoid aggregates. Such intratumoral lymphoid aggregates have both prognostic and therapeutic value, as they facilitate lymphocyte recruitment and help maintain both T-cell and B-cell antitumor responses.…”
mentioning
confidence: 99%
“…Of an initial cohort of 56 patients, 54 were treated with CTLA-4 inhibitor, and 7 of them responded (1). The non-responders were then treated with the PD-1 inhibitor, and 14 (28%) responded (1).…”
mentioning
confidence: 99%
“…Of an initial cohort of 56 patients, 54 were treated with CTLA-4 inhibitor, and 7 of them responded (1). The non-responders were then treated with the PD-1 inhibitor, and 14 (28%) responded (1). Using serial biopsies, the authors identified several tumor factors that favor response and resistance (1).…”
mentioning
confidence: 99%
See 1 more Smart Citation